Climatic conditions in the territory of the turkish kaganates in the early Middle Ages (Journal of history, 2020)
This article describes the natural conditions on the territory of the Turkish Kaganates in the early Middle Ages. Climate change study area are analyzed in the context of the general trends and patterns of the climate of the globe in the early Middle Ages. Attracted the effect of changes in natural conditions of life, the economy of the Turks. Also, the article based on the results of the research of scientists such sciences as history, archeology, geology, paleoclimatology, etc. Key words: nature, climate, climatic optimum, arid zone, Turkic khanates.